2010
DOI: 10.1183/09031936.00070509
|View full text |Cite
|
Sign up to set email alerts
|

Shift in sleep apnoea type in heart failure patients in the CANPAP trial

Abstract: In patients with heart failure (HF), the predominant type of sleep apnoea can change over time in association with alterations in circulation time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(31 citation statements)
references
References 22 publications
2
28
0
1
Order By: Relevance
“…14 -18 This is consistent with the observed inverse correlation between overnight change in LFV and mean PtcCO 2 and lowest SaO 2 during sleep. Our findings also help to explain why OSA and CSA can coexist in HF patients and why the predominant type can change over time, 8,9 possibly in relation to variations in the degree of fluid retention and overnight rostral fluid shift.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…14 -18 This is consistent with the observed inverse correlation between overnight change in LFV and mean PtcCO 2 and lowest SaO 2 during sleep. Our findings also help to explain why OSA and CSA can coexist in HF patients and why the predominant type can change over time, 8,9 possibly in relation to variations in the degree of fluid retention and overnight rostral fluid shift.…”
Section: Discussionmentioning
confidence: 67%
“…6,7 Despite their differing pathologies, patients with HF can have both types of sleep apnea, and the predominant type can shift from obstructive to central in association with a fall in PaCO 2 and an increase in circulation time, or vice versa. 8,9 These observations suggest that in HF, mechanisms for development of OSA and CSA may be linked.…”
mentioning
confidence: 93%
“…Many patients show a combination of different types of SDB breathing patterns that may change over the course of a night as well as over time 10. Although both OSA and CSA/CSR have been shown to be independent predictors of worse outcome in HF patients,11, 12, 13, 14, 15, 16 the different forms of SDB are likely to have different effects on the cardiovascular system 17.…”
Section: Introductionmentioning
confidence: 99%
“…A report from the recent clinical trial demonstrated a spontaneous conversion from predominantly CSA to OSA in 18% of a control group in association with a LVEF improvement. 5 Another study showed that improvement in cardiac function following cardiac transplantation in HF patients was accompanied by complete resolution of CSA or conversion to predominantly OSA. 2 The observations from both these reports, as well as our case, raise the possibility that, in patients with cardiac dysfunction, OSA and CSA may be part of the spectrum of periodic breathing, the pre-…”
Section: Discussionmentioning
confidence: 99%